Regional Autonomy in Indonesia: Challenges and Opportunities in Sustainable Development in the Era of Sustainable Development Goals (SDGs) - Dedi Mulyadi; Ega Puspita; Natasya Insani Auliarrahma; Shela Agnesia Shelvira; Ikhsan Kintara; Muh Syahdan Fauzi Abdul Fattah (Indonesian Journal Publisher, 2024)
Regional Autonomy in Indonesia is a very important part of government governance. Regional Autonomy is a concept that gives freedom and authority to regional governments to manage local resources and interests in accordance with the needs and characteristics of the region. Sustainable development referred to in the context of the Sustainable Development Goals (SDGs) requires attention to economic, social and environmental aspects simultaneously. In Indonesia, the challenges in achieving sustainable development goals are still very large. opportunities and challenges that arise from the implementation of Sustainable Development Goals (SDGs) in the regions need to be optimized and addressed as best as possible in a way that is well understood so that sustainable development goals can be achieved effectively.